Communication Strategies of Telkom Indonesia in Increasing ESG GoZero% Brand Awareness - Pramesti, Farida; Mukhlisiana, Lusy (Fakultas Ekonomi dan Ilmu Sosial Program Studi Ilmu Komunikasi Universitas AMIKOM Yogyakarta, 2025)
This study examines the communication strategy of PT Telkom Indonesia in enhancing brand awareness of its sustainability program, ESG GoZero%. The research is grounded in the urgency for the company to build a strong reputation and raise stakeholder awareness regarding the GoZero% initiative. This study aims to identify the communication strategies implemented by Telkom Indonesia to both internal and external audiences in promoting the ESG GoZero% program. Message reception is analyzed through the Elaboration Likelihood Model and Reception Theory. A qualitative approach with a case study method was used, and data were collected through in-depth interviews, observations, and documentation from seven informants. The findings reveal that internal communication strategies are carried out through internal media such as the company’s internal website, training sessions, and official memos. Meanwhile, external communication strategies utilize social media platforms and the corporate website. Telkom Indonesia applies a branding strategy that includes brand positioning, brand identity, brand personality, and brand communication, with a communication process structured into three stages: planning, implementation, and evaluation. The study concludes that structured and consistent communication, both internally and externally, successfully builds brand awareness of ESG GoZero% and strengthens the company’s reputation among stakeholders.